Pengaruh Sudut dan Kekasaran Pulley terhadap Torsi Sepeda Motor Matic 108 cm3 Tahun 2011 - Muhammad Rizqi Maulana; Syamsul Hadi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
A decline in performance in automatic motorcycles that have been used for a long time is a common problem caused by wear and tear on the Continuously Variable Transmission (CVT) system. This condition results in a reduction in the clamping force of the V-belt on the pulley, causing slippage and a decrease in transmission capacity. Based on the manufacturer's specifications, the torque is 8.32 Nm at 5500 rpm, while the test results show a torque of 7.41 Nm at 6500 rpm, a decrease of 10.9%. The study aims to analyze the effect of variations in pulley angle and surface roughness on the torque value of a 108 cm³ automatic motorcycle as a method to restore transmission performance without replacing the main components. The pulley angles tested were 14°, 13.8°, and 13.5°, while the surface roughness was varied based on the turning process with cutting inserts having nose radii of 0.2 mm, 0.4 mm, and 0.8 mm. The testing was conducted using a dynamometer at an engine speed range of 6000 – 9000 rpm. The results showed that the combination of a 13.8° pulley angle with a 0.2 mm cutting insert nose radius produced a torque of 7.41 Nm at 6500 rpm, an increase of 8.2% compared to the standard 14.5° configuration, which only produced 6.85 Nm. Modifying the pulley angle and surface roughness was proven to increase the V-belt clamping force, thereby improving transmission performance.